Short- and long-term prognostic value of hyponatremia in patients with acute coronary syndrome: A systematic review and meta-analysis. - Qiang-Qiang Ma; Xiu-De Fan; Tao Li; Yuan-Yuan Hao; Feng Ma (PLoS ONE, 2018)
Hyponatremia is relevant to heart failure, liver cirrhosis and stroke, but the prognostic value of serum sodium levels in patients with acute coronary syndrome are still unclear. So we did a systematic review and meta-analysis to assess the prognostic value of hyponatremia on adverse events in patients after ACS. We systematically searched PubMed, Embase and Cochrane Library to find literatures which studied the prognostic value of hyponatremia in patients with ACS. Our main endpoints were the all-cause mortality and heart failure in the short- and long-term. Of 369 identified studies, 20 studies were included in our analysis. Compared with the normal natrium, hyponatremia was significantly associated with the increased risks of all-cause mortality within 30 days (RR: 2.18; 95%CI: 1.96-2.42) and during the follow-ups (HR: 1.74; 95%CI: 1.56-1.942). For the second endpoint of short- and long-term heart failure, the pooled effect sizes in hyponatremia patients were 1.72(95%CI: 1.38-2.14) and 1.69(95%CI: 1.12-2.55) respectively. In conclusion, hyponatremia has a significant prognostic value for short- and long-term adverse event in patients after ACS, the dynamic monitoring of serum sodium levels may could help physicians to identify high risk ACS patients and to stratify risk for optimal management.